PEMANFAATAN HASIL HUTAN BUKAN KAYU (HHBK) PENGHASIL KERAJINAN TANGAN ANYAMAN OLEH MASYARAKAT DESA PANGKALAN BUTON KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Dahyanti, Dahyanti; Hardiansyah, Gusti; Sisillia, Lolyta (Universitas Tanjungpura, 2019)
UtilizationÂ of non-wood products for woven crafts isone of the pottentials in Pangkalan Buton Village, Sukadana Subdistrict, North Kayong Regency and becomes a raw material in making woven crafts. The research aims to obtain types of non-wood forest products for woven handicrafts and to describe the types of woven handicraft products by the people of Pangkalan Buton Village, Sukadana District. Research using descriptive qualitative methods. Data Collection is done by intetview, observation, and documentation. The results showed that there are 6 types of plants that are used by the community for woven crafts, namely bamboo rope (Gigantochloa apus), coconut (Cocos nucifera), nipah (Nypa fruticans), pandanus thorn (Pandanus tectoris) recam (Distranopteris linearis) and rattan candles (Calamus javensis). These types of planys are used as raw materials for woven crafts. Bamboo Reeds are into baskets and mistaken products. Coconut leaves are made into rattan products. Nipah leaf is made intoa woven roofing product. Pandan thom leaves are made into woven products for table mats, wallets, bags, pencil cases, tissues and mats. Resam rod is made into woven ring and bracelet products. Rattan rods are madeÂ into woven basket and cupboard products.Keyword: Non wood forest product, Types of plants, Woven crafts product, Utilization